'Unlocking the door to being there': The contribution of creative facilitators in supporting people living with dementia to engage with heritage settings. (January 2021) - Scholar, Helen; Innes, Anthea; Sharma, Monika; Haragalova, Jana
This article reports findings from the evaluation of 'Sensory Palaces', an innovative project developed by the charity Historic Royal Palaces, which looks after six of the United Kingdom's unoccupied royal palaces. The Sensory Palaces project employs creative facilitators to support people living with dementia and their care partners in engaging with two of these sites; Hampton Court Palace and Kew Palace. This paper focusses on the role and contribution of the creative facilitators in supporting people living with dementia to connect with these heritage spaces. It reports on data collected from facilitator interviews relating to the benefits of engaging together through sensory and creative methods to explore and share experiences of the palaces, drawing out important factors from the design, content and delivery of the sessions.